The effect of cold water immersion on physiological indices, inflammatory and immune responses during a soccer match - Park, S.; Hur, S.; An, K.; Kwon, Y.; Park, K.; Kim, J.; Lee, J. (The Korean Journal of Sports Medicine, 2021)
Purpose: We investigated the effects of cold water immersion (CWI) treatment during half-time break on performance related physiological indices during second half soccer match.